Assessing the Health-Related Outcomes and Correlates of Active Transportation in Children and Youth - Larouche, Richard (Université d'Ottawa / University of Ottawa, 2013)
Active school transport (AST; e.g. the use of non-motorized modes such as walking and cycling to travel to/from school) is an inexpensive, accessible and environmentally-friendly source of physical activity (PA). This dissertation addresses two overarching objectives: 1) to measure the relationships of AST with PA and health-related outcomes; and 2) to examine the correlates of AST immediately before and after the transition from primary to secondary school (the “school transition”). First, a systematic review revealed increasing evidence showing that AST is associated with greater daily PA levels, and that cycling to/from school is associated with higher cardiovascular fitness. Cycling for transportation (not only for school trips) was also associated with lower values for total cholesterol and total cholesterol/HDL cholesterol ratio in the nationally-representative 2007-2009 Canadian Health Measures Survey. Moreover, the present dissertation provides preliminary evidence suggesting that AST may help attenuate the decline in PA across the school transition. However, the relationship between AST and body composition indicators remains unclear. With respect to the correlates of AST, distance was the strongest barrier to AST at both time points, but several road safety concerns, and the perception of having too much stuff to carry were also associated with engagement in motorized travel. At follow-up, AST was more common in children whose parents owned less than 2 cars. In contrast, children were more likely to engage in AST if their parents reported that they chose to live in their current neighbourhood so that their children could walk or bike to school. The associations of neighbourhood walkability (as measured with the Walk Score® application) with AST and PA were generally stronger after the school transition. While AST may improve health among children and youth, an ecological approach targeting multiple levels of influence will likely be needed to alleviate current barriers to AST.
Keywords: active transport; physical activity; obesity; cardiovascular fitness; correlates; social-ecological model; transport actif; activité physique; obésité; capacité cardiovasculaire; déterminants; modèle socio-écologique